2020
DOI: 10.1016/j.cca.2020.05.027
|View full text |Cite
|
Sign up to set email alerts
|

The underlying changes and predicting role of peripheral blood inflammatory cells in severe COVID-19 patients: A sentinel?

Abstract: Background: The underlying changes of peripheral blood inflammatory cells (PBICs) in COVID-19 patients are little known. Moreover, the risk factors for the underlying changes of PBICs and their predicting role in severe COVID-19 patients remain uncertain. Material and methods: This retrospective study including two cohorts: the main cohort enrolling 45 patients of severe type serving as study group, and the secondary cohort enrolling 12 patients of no-severe type serving as control group. The PBICs analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
2
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(109 citation statements)
references
References 48 publications
4
90
2
6
Order By: Relevance
“…After full‐text review, 16 articles were selected for quantitative synthesis (Table 1). 18‐33 The median or mean age ranged from 35 to 67 years old with a mortality rate from 0% to 50%. Male predominance was found in 10 studies.…”
Section: Resultsmentioning
confidence: 99%
“…After full‐text review, 16 articles were selected for quantitative synthesis (Table 1). 18‐33 The median or mean age ranged from 35 to 67 years old with a mortality rate from 0% to 50%. Male predominance was found in 10 studies.…”
Section: Resultsmentioning
confidence: 99%
“…G, In the case of vertical transmission of SARS-CoV-2, anticipated complications might involve infection of the placenta (chorioamnititis, premature membrane rupture), and adverse neonatal outcomes, such as stillbirth, neonatal asphyxia, pneumonia, and neonatal death COVID-19 patients might be caused by the pulmonary recruitment of immune cells from peripheral blood and the infiltration of lymphocytes into the airways as suggested by several authors. [33][34][35][36] The release of pro-inflammatory cytokines (such as IFN-γ and IL-6) and chemokines (such as CCL2 and CXCL10) attracts immune cells, notably monocytes and T lymphocytes, but not neutrophils, from the blood to the infected site. 22,37 This will result in lymphopenia, eosinopenia, and increased neutrophil-lymphocyte ratio in peripheral blood, 38,39 as well as ARDS in COVID-19 patients.…”
Section: Impaired Adaptive Immune Responses In Covid-19 Patientsmentioning
confidence: 99%
“…Most of our included studies found signi cant lower levels of immune cells (CD8 + T, CD4 + T, CD3 + T, B and NK cells) in severe cases compared with mild cases [2,8,12]. Only two studies reported no signi cant decrease in CD8 + T cell level [3,16], while one study reported higher levels of B cell [11] in severe cases. Synthesizing all the collected evidence, our meta-analysis results found that the levels of immune cells (CD8 + T, CD4 + T, CD3 + T, B and NK) were signi cantly lower in severe cases compared with mild cases, but Treg cell level and CD4 + /CD8 + ratio showed no signi cant differences.…”
Section: Discussionmentioning
confidence: 89%